Association between 25-hydroxyvitamin D levels and COVID-19 severity. (June 2022) - Takase, Tomoki; Tsugawa, Naoko; Sugiyama, Takayuki; Ikesue, Hiroaki; Eto, Masaaki; Hashida, Tohru; Tomii, Keisuke; Muroi, Nobuyuki
Summary: Background and aims: Despite reports on the impact of vitamin D status on coronavirus disease 2019 (COVID-19) severity, the association between low vitamin D status and severe COVID-19 remains unclear. Moreover, researchers have not determined the aforementioned association in Japanese patients. This study aimed to investigate the association between 25-hydroxyvitamin D [25(OH)D] levels and COVID-19 severity in Japanese patients. Methods: This retrospective observational study included 117 consecutive patients with COVID-19 admitted to the Kobe City Medical Center General Hospital between October 01, 2020, and January 31, 2021. We measured the serum 25(OH)D levels using blood specimens collected within 5 days of hospital admission using liquid chromatography-tandem mass spectrometry. Results: There were 21 (17.9%), 73 (62.4%), 19 (16.2%) and 4 (3.4%) patients with severe deficiency (<10 ng/mL), deficiency (10–<20 ng/mL), insufficiency (20–<30 ng/mL), and sufficiency (≥30 ng/mL) of vitamin D, respectively. In univariate logistic regression analyses, lower serum 25(OH)D levels [odds ratio (OR) 1.18 per 1 ng/mL decrease, 95% confidence interval (CI) 1.04–1.33, p = 0.007] were significantly associated with invasive mechanical ventilation (IMV) or death. In a multivariate logistic regression analysis, low serum 25(OH)D levels [OR 1.22 per 1 ng/mL decrease, 95% CI 1.06–1.40, p = 0.005] were significantly associated with IMV or death. The cut-off value of serum 25(OH)D levels was 10.4 ng/mL, calculated by the receiver operating characteristic curve to detect the requirement for IMV or death. Conclusions: To the best of our knowledge, this is the first study to assess the association between vitamin D status and COVID-19 severity in Japanese patients. Low serum 25(OH)D level was detected as an independent risk factor for severe COVID-19 among Japanese patients.